2022
DOI: 10.1016/j.cub.2021.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis pavement cell shape formation involves spatially confined ROPGAP regulators

Abstract: How cells acquire complex shapes is a fundamental question in biology. Lauster et al. show that PHGAP/RENs associate with cortical microtubules preferentially along anticlinal cell faces, and they facilitate the spatially distinct deactivation of ROP2 in indentations. This interplay is essential for multipolarity of epidermal pavement cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 76 publications
(133 reference statements)
1
26
0
Order By: Relevance
“…Indeed, PHGAP deletion mutants lacking the non-catalytic domains were unable to complement the phgap1phgap2 mutant and did not properly localize in pavement cells. 51 Similarly, the C-terminal part of the close PHGAP homolog, REN1, containing coiled-coil domains and active in continuous tip growth, was not essential for the GAP activity, but was needed for the apical REN1 localization in the pollen tubes. 36 Post-translational regulation of GAPs had previously not been reported in plants, whereas in mammalian cells a number of GAPs are known to be regulated by phosphorylation that can affect either their GAP activity or their subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, PHGAP deletion mutants lacking the non-catalytic domains were unable to complement the phgap1phgap2 mutant and did not properly localize in pavement cells. 51 Similarly, the C-terminal part of the close PHGAP homolog, REN1, containing coiled-coil domains and active in continuous tip growth, was not essential for the GAP activity, but was needed for the apical REN1 localization in the pollen tubes. 36 Post-translational regulation of GAPs had previously not been reported in plants, whereas in mammalian cells a number of GAPs are known to be regulated by phosphorylation that can affect either their GAP activity or their subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…However, BIN2 might not affect the anticlinal cell wall localization of PHGAP2 by direct phosphorylation. It has been shown that the indentation enrichment of PHGAPs depends on MTs, 51 of which the protein stability is regulated by BIN2 phosphorylation. 38 It remains to be determined whether BIN2 regulates the indentation enrichment of PHGAP2 through phosphorylation and stabilization of MTs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations